Enhancing Public Services Through Residential Area Management: A Public Administration Study on the Implementation of the Regional Development and Housing Plan (RP3KP): RP3KP - trenggana, widaningsih; Muchtar; Pundenswari, Pupung (Ilomata International Journal of Social Science, 2025)
Improving public services is the primary goal of governance, which is focused on community welfare. One critical sector in enhancing the quality of public services is residential area management. This article examines the role of residential area management in supporting public service improvement, focusing on implementing the Regional Development and Housing Plan (RP3KP) in Tana Tidung Regency. The study aims to analyze the contribution of RP3KP to public service improvement in the housing sector and identify key success factors and challenges in its implementation. This research employs a qualitative approach with a case study method. Data was collected through policy document analysis, interviews with relevant stakeholders, and field observations. The results indicate that RP3KP has positively contributed to improving the quality of public services in the housing sector through integrated and participatory planning. The successful implementation of RP3KP is influenced by policy synergy between central and local governments, active community involvement in planning, and effective coordination among local government agencies. However, this study also identifies several challenges, such as limited resources, inadequate spatial data, and difficulties in cross-sectoral coordination. The implementation of RP3KP can potentially become a strategic model for optimizing public services in the housing sector, provided it is supported by consistent policies, efficient resource management, and enhanced institutional capacity. Practical recommendations for local governments include strengthening residential area management as an integral part of inclusive and sustainable public services.